The impact of zakat, infak, and sedekah funds, life expectancy, and average length of schooling on poverty mediated by economic growth in Indonesia - Ayati, Nufasilul; Siswanto, Siswanto; Khusnudin, Khusnudin (Journal of Islamic Economics Lariba, 2025)
IntroductionDespite Indonesia’s commitment to poverty alleviation through human development and Islamic social finance, regional poverty disparities persist. While life expectancy and education have been widely studied, the effectiveness of zakat, infak, and sedekah in reducing poverty remains underexplored in empirical development research.ObjectivesThis study investigates the effects of zakat, infak, and sedekah (ZIS), life expectancy, and the average length of schooling on poverty in Indonesia’s provinces, while assessing the mediating role of economic growth in these relationships.MethodA quantitative panel data approach was employed using secondary data from 33 Indonesian provinces spanning 2019 to 2023. Panel regression models were estimated with EViews to examine direct and indirect effects among variables and test mediation through economic growth.ResultsThe findings reveal that life expectancy significantly reduces poverty both directly and through economic growth. Economic growth also independently contributes to lowering poverty levels. However, the distribution of ZIS showed no significant influence on poverty, suggesting institutional or structural limitations. Unexpectedly, average years of schooling were positively correlated with poverty, indicating possible mismatches between educational attainment and labor market demands.ImplicationsThe results underscore the need to improve the governance and strategic alignment of Islamic social finance with regional development. They also highlight the importance of shifting education policy from quantity to quality and ensuring inclusive, health-driven economic growth.Originality/NoveltyThis study integrates Islamic social finance and human capital within a poverty reduction model, offering new empirical insights into the pathways through which social and economic variables interact in Indonesia’s development context.